Effect of Oral Health Promotion on Caries Experience and Oral Cleanliness of School Children in Kerung, Nepal: A Prospective 6-month Follow-Up Study - Martens, Luc; Cauwels, Rita; Vandenbulcke, Jeroen; Joshi, Kumbh Raj; Pradhan, Shaili; Lambert, Martijn (Journal of Nepal Health Research Council, 2021)
Background: A longitudinal oral health promotion project on caries experience and oral cleanliness was performed in a remote village in Nepal. The aim of this 6-month prospective survey was to investigate the impact of an oral health promotion project on caries experience, oral health-related behaviour, and general knowledge about oral health in Kerung, a remote village in Nepal. Methods: A prospective study was conducted in a convenience sample of children from the local school in Kerung. At baseline and after six months, dental plaque scores and caries experience scores were measured by calibrated examiners. Validated questionnaires on oral health habits and knowledge on oral health were taken. In addition, an oral health promotion program was developed. Results: At baseline, 359 children were included, of which 266 could be surveyed after six months. A statistically significant decrease in the mean plaque score was found at after six months with a higher reduction for boys. A significant decrease in caries prevalence, as well as a significant increase in knowledge about oral health, was observed. Furthermore, after six months there were significantly more children reporting that they brushed their teeth for at least two minutes. Conclusions: Dental screenings and a comprehensive educational program resulted in a significant improvement of oral health. Keywords: Caries experience; Nepal; oral cleanliness; oral health promotion